PLURIMOBIL – MATERIAŁY DYDAKTYCZNE WSPOMAGAJĄCE MOBILNOŚĆ W SZKOLNICTWIE ZAWODOWYM - Czura , Anna (Neofilolog, 2013)
Mobility in vocational education and training (VET) is believed to have a positive impact on the development of professional skills, key competences and language proficiency. However, there are more and more voices indicating that participation in mobility may not automatically translate into an in-creased level of intercultural and linguistic skills. To enhance the educational benefit of mobility programmes, there is a need to develop measures which offer intercultural preparation and guidance. The main purpose of this article is to present the objectives and projected outcomes of the PluriMobil project, which aims to create a coherent pedagogical instrument to help secondary vocational school teachers prepare their learners for participation in different types of learning mobility.